Comparison of NIR powders to conventional fingerprint powders. (November 2021) - Chadwick, Scott; Cvetanovski, Madeleine; Ross, Matthew; Sharp, Antonia; Moret, Sebastien
Highlights: NIR powders were compared to conventional black and luminescent powders. Black and GREENcharge™ powders are the most effective powders on the surfaces tested. NIR powders do not offer significant advantage on conventional substrates. Universal Powder outperformed fpNATURAL 1® in NIR luminescent conditions. Abstract: Fingerprint powders remain one of the most common detection techniques used at the crime scene. However, powder efficiency and contrast can be hindered when applied to highly patterned backgrounds. This problem can be overcome using powders that are luminescent in the near-infrared (NIR) region of the electromagnetic spectrum. Despite being commercially available, those powders have been the focus of only a small number of studies, limited to a few substrates or donors. Their performance and advantages over common techniques are still to be thoroughly investigated. This study aims at assessing the performances of two NIR powder (fpNATURAL 1® and Universal Powder an in-house developed powder) against two conventional powders, a black and a luminescent powder (Sirchie Black, GREENcharge™) under various optical conditions (white light, visible luminescence and NIR luminescence). The powders were compared on four substrates using fingermarks of four different ages from five donors. A total 900 fingermarks were collected for each pairwise comparison. NIR imaging provided good background suppression and a high contrast, however it was shown that conventional powders remained the most effective powdering methods on the substrates tested as sufficient contrast could be achieved under white light or in luminescent mode in the visible region. The results showed that Universal Powder performed similarly to conventional powders, but poor performances were obtained on most substrates with fpNATURAL 1®. Based on the results obtained, it is recommended to use NIR powders only on substrates or conditions where traditional powders are known to perform poorly.